Ethico-Political Dilemmas of a Community Oral History Project: Navigating the Culture of the Corporate University - Cuádraz, Gloria H. (Social justice, 2011)
The article discusses the ethical and political issues related to the funding and planning of a community history project conducted by university researchers. The author describes her experiences conducting a community oral history project that partnered her university with community organizations. In addition, she discusses how globalization has effected the research and educational functions of universities, noting the increased use of a corporate model and citing Arizona State University (ASU) as an example.